Meaning of Teacher Thinking in Curriculum Transaction - Kumar, N. Suresh (Voices of Teachers and Teacher Educators, 2017)
Programs for teacher education are developed to prepare educators at various educational levels. Preschool, elementary, and secondary education programs vary, as do those pertaining to special education needs, health, physical education, and similar subjects. These programs’ course components are intended to give them a professional feel. For instance, field experience that is integrated with other elements gives trainees more opportunities for professional interaction. The internship is a crucial and integral component of the course that offers the much-needed opportunity for field experience.